Increasing Knowledge of Public Mothers About Early Breastfeeding Initiation (IMD) Post Delivery - Suryati; Ulfa, Siti Maria; Wulandatika, Darmayanti (OMNICODE Journal (Omnicompetence Community Developement Journal), 2021)
The low implementation of early initiation of breastfeeding (IMD) in postpartum mothers is due to several things, including the lack of information and knowledge that must be done about correct breastfeeding techniques, obstacles related to services at the place of delivery and the lack of support provided by family members. The aim of the program is to increase the knowledge of postpartum mothers about early initiation of breastfeeding (IMD) after childbirth in Sungai Lulut Village. Method of Implementation: This activity uses the method of Counseling and Questions and Answers about increasing postpartum mother's knowledge about early initiation of breastfeeding (IMD) after delivery. Results: After the implementation of this community service activity. The conclusion is that there is an increase in knowledge of postpartum mothers about the implementation of IMD.